Intrauterine Programming of Cardiovascular Diseases in Maternal Diabetes - Higa, Romina; Leonardi, María Laura; Jawerbaum, Alicia (Frontiers in Physiology, 2021)
Maternal diabetes is a prevalent pathology that increases the risk of cardiovascular diseases in the offspring, the heart being one of the main target organs affected from the fetal stage until the adult life. Metabolic, prooxidant and proinflammatory alterations in the fetal heart constitute the first steps in the adverse fetal programming of cardiovascular disease in the context of maternal diabetes. This review discusses both human and experimental studies addressing putative mechanisms involved in this fetal programming of heart damage in maternal diabetes. These include cardiac epigenetic changes, alterations in cardiac carbohydrate and lipid metabolism, damaging effects caused by a prooxidant and proinflammatory environment, alterations in the cardiac extracellular matrix remodeling, and specific signaling pathways. Putative actions to prevent cardiovascular impairments in the offspring of mothers with diabetes are also discussed.